The center seat : 55 years of Star Trek [videorecording (DVD)] - Nimoy, Leonard; Wheaton, Wil; Spiner, Brent (Mill Creek Entertainment, 2023)
This multi-episode documentary series takes viewers on the definitive in-depth journey behind the scenes of one of the greatest landmark franchises of all time: Star Trek. Celebrating the show's 55th anniversary, each episode focuses on a different chapter in the groundbreaking program's history. Interviews with the cast, crew, and experts including one of Leonard Nimoy's final in-depth Trek interviews reveal never-before-heard backstage stories and offer fresh insights. The Center Seat details how Star Trek began, where it's been, and how it₂s boldly going where no television series has gone before!